Do Healthcare Professionals Comprehend Standardized Symbols Present on Medical Device Packaging?: An Important Factor in the Fight Over Label Space. Issue 3 (14th April 2016) - Seo, Do Chan; Ladoni, Moslem; Brunk, Eric; Becker, Mark W.; Bix, Laura
Abstract : Objective: Evaluate the ability of healthcare providers from the US to comprehend internationally standardized symbols placed on medical device packaging.Participants: Eighty‐six healthcare providers attending the Association of Surgical Technologists (AST) Instructors' Forum (Savannah, GA February 2014), the 46th Annual AST National Conference (Denver, CO May 2014), or members of the same organization that responded to a targeted email blast.Measures: We adapted the comprehension portion of ISO 9186‐1: 2007 to test 38 standardized symbols developed for the medical device industry. Participants were asked to provide an open‐ended response regarding the meaning of each symbol. Survey responses were categorized into five levels of comprehension: correct, wrong, opposite, don't know or no response. Symbols receiving response rates of ≥85% in the correct category were considered successful. Conversely, if responses categorized as opposite were ≥5%, symbols were considered 'critically confusing.'Main Results: Six of 38 symbols were classified as 'successful'; five of the six had text (in English) imbedded within. Three out of the 38 were categorized as 'critically confusing'; they were not only misunderstood, but, in fact, interpreted to mean the opposite of what was intended by ≥5% of participants surveyed.Conclusions: Given that the medical device industry in the US has requested permission from the US Food and Drug Administration (FDA) to use stand‐alone symbols to better harmonize with EU Directives, the exploration of healthcare providers' comprehension of the same is an important and timely topic. Our work suggests that symbols commonly incorporated into the labeling of medical devices may not be readily understood at present. As such, policy decisions should be carefully considered.Limitations: Although we provided participants with a general context of use (i.e. these symbols are used on medical devices), the specific part of the hospital, or type of procedure where the symbol would be found was not noted. Further research to evaluate symbol comprehension with specific context (e.g. IVD, general procedure, etc.) is recommended. Run order was presented consistently throughout the experiment in the same booklet. We tested whether or not this impacted results in two ways: (a) by correlating run order with mean performance to see if there was a trend through the data (toward improvement or decline) and (b) by assuming repeated measures from subjects to test if the subject response changes with time. Neither of these analyses suggested significant effects because of run order. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Given that the medical device industry in the USA has requested permission from the US Food and Drug Administration (FDA) to use stand‐alone symbols to better harmonize with EU Directives, the exploration of healthcare providers' comprehension of the same is an important and timely topic. Our work suggests that symbols commonly incorporated into the labeling of medical devices may not be readily understood at present. As such, policy decisions should be carefully considered.